Deep time evolution of the Latitudinal Diversity Gradient: Insights from mechanistic models - Manon Lorcery; Laurent Husson; Tristan Salles; Sébastien Lavergne; Oskar Hagen; Alexander Skeels (PLoS ONE, 2025)
The latitudinal diversity gradient (LDG) designates the increase in species richness toward the tropics. While geological and climatic changes are recognized as key drivers, the precise factors and their relative contributions to species richness gradients remain debated. Using a spatially explicit eco-evolutionary model, we simulate diversification over 125 million years. We validate the model with empirical mammalian richness patterns, and uncover a pivotal role of paleoclimate and paleogeography. This approach allows us to investigate both the mechanisms driving the LDG and space and time variations in species diversification rates across dynamic landscapes integrating changes in tectonic, climatic and surface processes. We show how scale-dependent surface processes are a key driver of regional diversity patterns and how LDG can emerge under a wide range of eco-evolutionary scenarios. Plate tectonics and the subsequent enduring uneven distribution of land masses within the North and South hemispheres imprinted an asymmetric pattern of species diversification rates, primarily shaped by paleoclimate and paleogeography and only to a lesser extent by surface processes. Our simulations also indicate that the LDG has persisted since the Cretaceous, steepened and stabilized from the early Cenozoic on. The modeled scenarios depict that species primarily originate in the tropics and disperse toward the poles without losing their tropical presence. The tropics not only served as a cradle, fostering the origination of new species, but also as a museum, preserving biodiversity over deep time.